Constructing concepts without feedback: An empirical investigation of how relational information affects multidimensional concept completion behavior in an unsupervised task - Charles A. Doan; Ronaldo Vigo (PLoS ONE, 2025)
The ability of humans to intentionally learn, without feedback, unidimensional stimulus relations in categorization tasks has been empirically established over the past two decades. However, whether observers can learn more complex multidimensional stimulus relations across these unsupervised tasks has not yet been determined. We demonstrate across an unsupervised concept completion experiment that the failure to observe multidimensional learning in previous experiments may be attributable to factors such as increased stimulus or task complexity. We posit that concept completion is related to category learning in that it reveals the underlying tendencies that are associated with some categories being easier to learn than others. In our experiments, we found observers readily learned to complete a two-dimensional exclusive-or concept, evidenced by an increase in object selection as the task progressed with a decrease in choice response times. We also found that observers readily learned to complete, as evidenced by similar patterns in object selection and response time behavior, a more complex three-dimensional stimulus relation that has empirically been associated with large amounts of categorization errors in related supervised classification tasks. Accordingly, we tested two existing formal models to determine their ability to account for our observations: namely, the Simplicity Model and the Generalized Representational Information Theory (GRIT) basic measure. We show how relational information processing as expounded in GRIT accounts for the observed completion behavior. Overall, our findings show how people gravitate, in a gradual and composite fashion, towards minimizing the perceived complexity of categories as much as possible.